BUNUH DIRI MERUSAK ANUGERAH HIDUP DARI ALLAH BANDINGKAN KEJADIAN 2:7 - Joro, Imanuel; Tomhisa, Resky (Pineleng Theological Review, 2025)
This article discusses the act of suicide and how the Catholic Church views suicide in relation to the meaning of life as stated in Genesis 2:7. Suicide is an undeniable human act, even within the Catholic Church. It can be said that the phenomenon of suicide is a common occurrence that can happen to anyone, regardless of background. Various cases of suicide occur throughout the ages. People seem to despise the life bestowed by the Creator. Life becomes meaningless. Therefore, this article aims to present the reasons for suicide and demonstrate that life is a gift from the Creator, based on Genesis 2:7, which must be protected and cared for because life has meaning and purpose.